Portfolio Management Practices Among Financial Professionals: An Analysis of Investment Strategies and Risk Preferences - Rajgarhia, Nipun; Bajpai, Amit (Journal of Global Economy, Business and Finance, 2026)
Effective portfolio management is crucial for professionals who seek financial stability and growth. This study examines the investment behavior, risk tolerance, and asset allocation strategies of selected urban professionals in Coimbatore District. By analyzing their preferences across various investment avenues, this research highlights the factors influencing their decisions and the challenges they face in managing their portfolios. The findings contribute to a deeper understanding of financial planning trends and provide insights for financial advisors and policymakers to enhance financial literacy and investment awareness.